آثار الأزمة الاقتصادية على العمل والأجر في الفقه الإسلامي والقانون - الجيلاني, علي حسين (Gezira Journal of Economic and Social Sciences, 2022)
جاءت أهمية الدراسة من أهمية العمل والأجر وما يتبعهما من تنظيم قانوني في الفقه الإسلامي والتشريعات الوضعية في الظروف العادية من حماية وآليات تحفظ حقوق الطرفين في العلاقة العمالية، الأمر يحدث تغيير كبير في تأثيرات الأزمة الاقتصادية على كل من العمل والأجر أثر الاختلالات التي تنجم عنها من تدعيات تؤثر في العمل والأجر وبل وقد تؤدى إلى فقدان الحق أو ضياع الحماية المقررة قانوناً لهما. هدفت هذه الدراسة إلى التعّرف على الأزمة الاقتصادية وتأثيرها على الجوانب الاقتصادية والسياسية والاجتماعية، ومعرفة تأثير الأزمة الاقتصادية على العمل وطرق تدخل الدول لمعالجة الآثار السلبية، وتناول الآثار السلبية للازمة الاقتصادية على الأجر وما يمكن أن يؤدى إليه من اختلالات. انتهجت الدراسة المنهج الاستقرائي التحليلي، والمنهج المقارن. توصلت الدراسة إلى عدة نتائج وتوصيات، أهم النتائج أن من أبرز آثار الأزمة الاقتصادية تفشي مشكلة البطالة، وما تؤدي له من إهدار للموارد البشريَّة، وضياعاً للوقت، والجهد والطاقة، كما أنَّ البطالة تؤدي إلى إهدار أحد الحقوق الأساسيَّة للفرد، وهو الحق في العمل، وذلك أن العمل يشعر الفرد بأهميته في المجتمع الذي يعيش فيه، كما أن الإسلام في معالجته للأزمة الاقتصاديَّة، قد وضع منهجاً واضحاً في قضية البطالة، وسعى إلى معالجتها بطريقة فعَّالة وذلك عبر إلزام الدَّولة بتهيئة العمل للقادرين عليه. بينما جاءت أهم التوصيات ضرورة التدخل من جانب الدول في وقت مبكر من وقوع الأزمات الاقتصادية وذلك للتخفيف من شدة آثارها المحتملة قبل تفاقمها عبر إجراءات قانونية واقتصادية ومالية، والابقاء على المؤسسات والشركات والتي تستخدم الأيدي العاملة ومساعدتها خلال فترة الأزمة الاقتصادية مساهمة في حل مشكلة البطالة. The importance of the study came from the importance of work and wages, and the legal regulation that follows them in Islamic jurisprudence and statutory legislation in normal circumstances, from protection and mechanisms that preserve the rights of the two parties in the labor relationship, a major change occurs in the effects of the economic crisis on both work and wages, the impact of the imbalances that result from it It affects work and wages, and may even lead to the loss of the right or the loss of the protection legally prescribed for them. This study aimed to identify the economic crisis and its impact on the economic, political and social aspects, and to know the impact of the economic crisis on work and the methods of countries ’intervention to address the negative effects, and to address the negative effects of the economic crisis on wages and the imbalances that could lead to it. The study followed the inductive analytical approach and the comparative approach. The study reached several results and recommendations, the most important results are that the most prominent effects of the economic crisis are the widespread unemployment problem, and its waste of human resources, waste of time, effort and energy, and unemployment leads to wasting one of the fundamental rights of the individual, which is the right to work, and that That the work feels the importance of the individual in the society in which he lives, just as Islam in its treatment of the economic crisis has set a clear approach in the issue of unemployment, and sought to address it in an effective way by obliging the state to prepare work for those who are able to do it. While the most important recommendations were the necessity of intervention by states early in the occurrence of economic crises in order to mitigate the severity of their potential effects before their exacerbation through legal, economic and financial measures, and to maintain the institutions and companies that use manpower and help them during the economic crisis, to contribute to solving the unemployment problem.